Efeito da fonte de óleo da dieta sobre o desempenho zootécnico, perfil lipídico e características sensoriais do camarão Litopenaeus vannamei cultivado em condições de alta salinidade - Castro, Otavio Serino (2010)
The white shrimp L. vannamei is considered a euryhaline species able to perform hypo and hyper-osmoregulation. Despite this ability, its growth performance under culture can be compromised when water salinity exceeds 40‰. This study aimed at evaluating the effect of oil source and the levels of polyunsaturated fatty acids (PUFA) in the diet on the performance, resistance, lipid profile and sensory characteristics of the tail of juvenile L. vannamei reared under high salinity. In the first study phase, 2.79 ± 0.60 g shrimp were reared for 64 days under an optimal (SIdeal, 23 ± 1,2‰) and high (SAlta, 44 ± 2,0‰) water salinity. Animals were fed diets with similar composition and nutritional characteristics, except in regards to the polyunsaturated fatty acids (PUFAs) profile which varied according to the source and levels of oil inclusion: PXE (8.01% PUFA of the total lipid content of the diet), diet with 26.6 g/kg of fish oil and 10.0 g/kg of soybean oil; SJA (0.93% PUFA), 34.5 g/kg of oil soybean; KRL (6.93% PUFA), 48.3 g/kg of krill oil and 4.4 g/kg of soybean oil; KRL- (2.92% PUFA), 14.5 g/kg of krill oil and 21.2 g/kg of soybean oil; KRL+ (8.81% PUFA), 55.5 g/kg of krill oil and 3.8 g/kg of soybean oil. In the second study phase, 1.71 ± 0.4 g shrimp were subjected to three levels of osmotic stress. Initial water salinity at 30‰ was increased by 2, 3 and 4‰ per day (SAL_1, SAL_2 and SAL_3, respectively) for five consecutive days. Prior to the osmotic stress period, all animals were fed a diet deficient in PUFA (diet AGP_15 with 1.48% PUFA), followed by seven days feeding on their respective diets AGP_45, AGP_65 and AGP_85 (diets with 4.60, 6.61 and 8.61% PUFA, respectively). In the third study phase, sensory analysis was performed on shrimp which had been fed diets PXE, KRL, SJA and KRL + and grown under SAlta during the first study phase. Consumer preference for shrimp color, texture and flavor was carried out with 20 untrained tasters using the Best-worse scaling methodology. At the end of the first study phase, shrimp grown under SAlta reached a lower body weight than those under SIdeal (11.21 ± 2.05 g versus 11.56 ± 1.77 g, respectively). KRL diet promoted the fastest shrimp growth (1.01 ± 0.01 g/week) and body weight at harvest (11.97 ± 2.01 g), regardless of water salinity. Shrimp fed SJA reached a larger body weight compared to those fed PXE (11.18 ± 1.77 g versus 11.05 ± 1.83 g, respectively). There were no significant differences in shrimp survival (93.4 ± 5.07%) and yield (554 ± 68.5 g/m2) among different diets. Also, no significant interactions between salinity and diet were detected. In the second study phase, PUFA supplementation in the diet failed to promote an increase in resistance of L. vannamei against increments in water salinity. At the end of the rearing period, there was 100% mortality at 50 ± 0.7‰ final salinity (SAL_3), followed by 9.8 ± 2.2% survival for 44.8 ± 0.4‰ (SAL_2) and 67.1 ± 8.9% survival for 39.7 ± 0.5‰ (SAL_1). Lipid profile analysis revealed that shrimp fed diets with PXE, KRL and KRL+ had higher concentrations of PUFA in the tail compared to those fed diets SJA and KRL-. There was a higher consumer acceptance for shrimp that had been fed diets containing krill oil, compared to those fed fish or soybean oil. In general, the use of krill oil and PUFA enrichment in L. vannamei diets promoted a higher shrimp body weight under high salinity culture, and improved the sensory characteristics (color and flavor) of shrimp tails.